Kecerdasan emosional dan kualitas hidup: Meta-analisis - Rahmadi, M. Agung; Nasution, Helsa; Sari, Milna (Jurnal Psikologi Poseidon, 2024)
Emotional intelligence (EQ) has long been hypothesized to significantly influence quality of life; however, previous research has shown considerable variation in results due to the use of different measurement tools for these variables, despite employing the same theoretical foundation regarding emotional intelligence and quality of life. Therefore, the aim of this study is to analyze the relationship between EQ and quality of life through a meta-analysis of studies published between 2010 and 2020. The meta-analysis method in this study involved 25 studies (N = 7,523) that met the inclusion criteria. The results indicate a significant positive correlation between EQ and quality of life. Furthermore, the moderator analysis revealed that the measurement tools for EQ and the domains of quality of life significantly moderated the strength of the relationship between emotional intelligence and quality of life. The implications of these findings could serve as a discussion point in the context of developing intervention programs for emotional intelligence and quality of life, as well as providing a foundation for future relevant research directions.